An XRD and NMR crystallographic investigation of the structure of 2, 6-lutidinium hydrogen fumarate. Issue 22 (22nd May 2019) - Corlett, Emily K.; Blade, Helen; Hughes, Leslie P.; Sidebottom, Philip J.; Walker, David; Walton, Richard I.; Brown, Steven P.
Abstract : A crystallographic study highlighting the benefits of a combined XRD and NMR approach in investigating both stability and variation within an organic multicomponent crystal. Abstract : Fumarate is a pharmaceutically acceptable counterion often used to modify the biophysical properties of active pharmaceutical ingredients (APIs) through salt formation. With 2, 6-lutidine (2, 6-dimethylpyridine), fumaric acid forms the salt 2, 6-lutidinium hydrogen fumarate. An NMR crystallography approach was employed to investigate the salt structure and the intermolecular interactions involved in its formation and stability. The crystallographic unit cell was determined by both single crystal XRD (SXRD) and synchrotron powder X-ray diffraction (PXRD) to contract at low temperature with a skew in the β angle. Density functional theory (DFT)-based geometry optimisations were found partially to replicate this. A second room temperature structure was also identified which exhibited a similar skew of the β angle as the low temperature structure. DFT calculation was also employed, alongside 2D 1 H double-quantum (DQ) magic angle spinning (MAS) and 14 N– 1 H HMQC MAS NMR spectra, to investigate the hydrogen bonding network involved in the structure. DFT-based gauge-including projector-augmented wave (GIPAW) calculations highlighted both strong N + –H⋯O − and O–H⋯O intermolecular hydrogen bonds between the molecules, as well as several weaker CH⋯O hydrogen bonds. Both PXRD and solid-state MAS NMR, supported by thermal gravimetric analysis (TGA) and solution-state NMR analysis, show formation of fumaric acid within samples over time. This was evidenced by the identification of reflections and peaks associated with crystalline fumaric acid in the PXRD pattern and in 1 H MAS and 13 C cross polarization (CP) MAS solid-state NMR spectra, respectively.